Computer simulation and modeling of cartilage deformation during athletes` land training: One case study - Radakovic, R.; Filipovic, N.; Kosanic, D. (Serbian Journal of Sports Sciences, 2008)
The objective of this study was to make a computer model of athletes' land training and to determine the real deformation on the knee cartilage. A new algorithm is used for joint motion simulation, which visualizes sport specific motion data in athletes in a specific hip-joint model. Knee pain is a common problem for many sports people in the world. Knee injuries can be either internal (within the joint) or external (outside the joint). The knee is exposed to numerous weight bearing forces and does not cope with both weight bearing and twisting simultaneously, both of which often occur in sport. Anyone wearing boots with long studs will benefit from a better surface grip but this can hold the foot even when the player wants to change direction. The compression and shearing forces can result in menisci tears, knee ligament sprain and ruptures. Some mechanical properties of cartilage are well characterized, but little is known about its behavior in complex training. A finite element model of porous deformable media for cartilage is implemented. We used our own motion capture system to collect athletes' specific motion data. The system includes a computer, a camera and a number of colored markers. For unilateral gait analysis, 4 markers are attached to the athlete at various positions. Each color is identified by a different number. The computerized camera system captures the exact motion of these markers, which identifies the movement of the body while the athlete is running along a straight line. The aim of the study was to connect a 3D capture camera system with the estimation of cartilage deformation and stress during football players' standard test.